Pengaruh Agility Leadership dan Digital Culture terhadap Kinerja UMKM melalui Inovasi Model Bisnis - Nur Syakherul Habibi; Muhammad Yasir Zain; Alfi Hasaniyah; S Syaiful; Sofiyulloh Sofiyulloh (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of agility leadership and digital culture on the performance of batik SMEs in Pamekasan Regency with business model innovation as a mediating variable. Batik SMEs play an important role in the local economy but still face several challenges, including limited market access, low utilization of digital technology, and traditional managerial practices. This research employed a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to 108 batik SME owners and analyzed using Structural Equation Modeling (SEM). The results indicate that agility leadership and digital culture have a positive and significant effect on business model innovation. Furthermore, agility leadership and business model innovation significantly influence SME performance. Meanwhile, digital culture does not show a direct significant effect on SME performance. However, business model innovation mediates the relationship between agility leadership, digital culture, and SME performance. These findings suggest that improving SME performance requires not only digital technology adoption but also adaptive leadership capabilities and the development of innovative business models aligned with market dynamics.